Análise de viabilidade econômica da utilização de geradores a diesel em horário de ponta, considerando a probabilidade de falha dos equipamentos e risco da operação futura - Pinto, Fernando César (2015)
The increasing efforts to reduce energy consumption has established the special rates in higher consumption periods, called peak hours, a period defined by the distributor and approved by ANEEL for all its concession area, considering the load curve of your electrical system and composed of 3 (three) consecutive hours daily, except Saturdays, Sundays and holidays defined by federal law. Normative Resolution ANEEL. 482. The diesel generators, previously used only to address the lack of energy at the dealership, are a real possibility and easy to deploy. This article aims to analyze the economic feasibility for use of diesel generators in peak hours in the fibrocement industry, considering well as operational costs equipment reliability and the risk of failure in case of lack of energy Dealers among other issues involving the reliability engineering.